2020
DOI: 10.3389/fphar.2020.00162
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Prevents Acetaminophen-Induced Liver Injury by Promoting Autophagy

Abstract: Acetaminophen (APAP) overdose is a leading cause of drug-induced acute liver failure in clinical and hospital settings. Fisetin (FST) is a phenolic compound derived from natural products such as fruit and vegetables. Our research investigated the protective mechanisms of FST in APAP-induced hepatic injury in vitro and vivo. Assessment of mouse serum levels of alanine/aspartate aminotransferases (ALT/AST), liver myeloperoxidase (MPO) activity, malondialdehyde (MDA), glutathione (GSH), and reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Interestingly, upon oral administration, fisetin and its active metabolite, geraldol, get rapidly circulated to the blood vessels of the brain accompanied by slower dispersion into the brain parenchyma of mice and gets localized in the nucleoli of neuronal cells (28). Several biological benefits of fisetin include anti-inflammatory, cardioprotective, hepatoprotective, anti-cancer, and anti-diabetic effects (29)(30)(31)(32)(33). Preclinical studies have shown that fisetin protects against traumatic brain injury (TBI), aluminum chloride-induced neurotoxicity, and methylmercury-induced neurotoxicity owing to its anti-inflammatory property (34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, upon oral administration, fisetin and its active metabolite, geraldol, get rapidly circulated to the blood vessels of the brain accompanied by slower dispersion into the brain parenchyma of mice and gets localized in the nucleoli of neuronal cells (28). Several biological benefits of fisetin include anti-inflammatory, cardioprotective, hepatoprotective, anti-cancer, and anti-diabetic effects (29)(30)(31)(32)(33). Preclinical studies have shown that fisetin protects against traumatic brain injury (TBI), aluminum chloride-induced neurotoxicity, and methylmercury-induced neurotoxicity owing to its anti-inflammatory property (34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is considered to play an important role in the pathogenesis of various diseases (Doherty and Baehrecke, 2018 ). Increasing evidence shows that autophagy can regulate many key functions of the kidney in the normal and diseased state (Su et al, 2019 ; Zhang et al, 2020 ). STZ-induced autophagy is inhibited in the proximal and early tubules of DM rats, which is associated with renal tubular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, autophagy inhibition results in exacerbating skin inflammation and increased disease severity (Wu & Adamopoulos, 2017). Zhang et al (2020) revealed that acetaminophen-induced inflammation, apoptosis, and proliferation inhibition in the hepatocyte L-02 cell line could be enhanced by inhibiting autophagy and rescued by activating autophagy, respectively. They showed that the inhibition of autophagy in hepatocytes increased inflammation cytokines including IL-18 and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…ATG5-mediated autophagy is crucial for a wide range of biological processes, including DNA damage, cell proliferation, apoptosis, inflammation, differentiation, and drug resistance ( Han et al, 2020 ; Kim et al, 2020b ; Peng et al, 2019 ; Yue et al, 2019 ). The inhibition of autophagy might induce an increase in cell apoptosis and inflammation and a reduction in cell proliferation in hepatocytes ( Wu & Adamopoulos, 2017 ; Zhang et al, 2020 ). Also, autophagy inhibition results in exacerbating skin inflammation and increased disease severity ( Wu & Adamopoulos, 2017 ).…”
Section: Discussionmentioning
confidence: 99%